Improved Accuracy for Forensic Investigation Using SIFT-Based Copy-Move Forgery Detection - Yasir Muin; Amal Khairan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Digital photo manipulation is a significant issue in the current technological age, specifically due to the prevalence of social media and the availability of editing software. This presents a significant danger to the legal system as it has the potential to influence judges' decisions. Hence, the identification of image forgery is crucial in the realm of digital forensics to verify the authenticity of images and aid in investigative processes. One potential method for forensic analysis is the utilization of copy-move detection (CMFD). This method is used to identify instances where objects in an image have been copied or rearranged. The SIFT algorithm is one of several algorithms that can be utilized in CMFD. This algorithm is capable of identifying distinct characteristics within an image and comparing these characteristics to identify areas of duplication. Copying and moving forgeries can be effectively detected through the use of the SIFT algorithm. This algorithm offers the benefit of producing precise outcomes by comparing key point values. The test results can be shown as forensic digital proof of copy-move manipulation actions. This is further supported by validating the hashing values to confirm the results of the SIFT algorithm